Vampire weekend - Chen, Mike (Mira, 2023)
When Ian, a long-lost teenage relative, finds her, Louise Chao, punk rock vampire extraordinaire, feels a connection for the first time in ages, but when he discovers her true identity, he asks her for the ultimate favor--one that might change everything vampires know about life and death forever.